2004
DOI: 10.1148/radiol.2312030167
|View full text |Cite
|
Sign up to set email alerts
|

Are Two-dimensional CT Measurements of Small Noncalcified Pulmonary Nodules Reliable?

Abstract: Two-dimensional CT measurements are not reliable in the evaluation of small noncalcified pulmonary nodules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
178
4
14

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(201 citation statements)
references
References 16 publications
5
178
4
14
Order By: Relevance
“…Volume for all nodules was calculated based on nodule diameter (V = 1/6 * * [ab 2 ], with a the longest and b the perpendicular diameter). Especially in sub-solid nodules, but also in solid nodules, diameter measurements are less accurate than volume measurements [7,8]. Furthermore, the study used relatively thick slice-thickness (3.75-5 mm) and large reconstruction intervals (5 mm) that may have contributed to even more imprecise diameter measurements, especially for sub-centimeter nodules.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Volume for all nodules was calculated based on nodule diameter (V = 1/6 * * [ab 2 ], with a the longest and b the perpendicular diameter). Especially in sub-solid nodules, but also in solid nodules, diameter measurements are less accurate than volume measurements [7,8]. Furthermore, the study used relatively thick slice-thickness (3.75-5 mm) and large reconstruction intervals (5 mm) that may have contributed to even more imprecise diameter measurements, especially for sub-centimeter nodules.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, lung cancer growth patterns were only visually evaluated and not quantified. In the Dutch-Belgian randomized lung cancer screening trial (Dutch acronym: NELSON), nodule volumes were generated semi-automatically by software; a far more accurate way to determine nodule size [7,8]. In addition, for subsequent screening rounds VDTs were determined based on nodule volume [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…For the evaluation of solid pulmonary nodules three-dimensional volumetric assessment has been shown to be more accurate than two-dimensional measurements [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Other disadvantages of X-ray analysis include inability to identify small-area ossifications and to accurately locate the ossification. When evaluating a pulmonary nodule, 3D measurement is more reliable in determining changes in growth [12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Recent technical improvements in computed tomography (CT)-based three-dimensional (3D) imaging analysis have made accurate 3D measurement of OPLL possible [5,11]. Previous studies on lung cancer growth found that evaluation of the growth of lung cancer using a 3D measurement method was more reliable than using a 2D method [12][13][14][15]. The present study was designed to evaluate the accuracy of a novel CT-based method of 3D analysis we had previously devised, to measure changes in the volume of OPLL.…”
Section: Introductionmentioning
confidence: 99%